Students as co-producers in a multidisciplinary software engineering project: addressing cultural distance and cross-cohort handover - Foster, David; Gilardi, Filippo; Martin, Paul; Song, Wei; Towey, Dave; White, Andrew (Taylor & Francis, 2018)
This article reports on an undergraduate software engineering project in which, over a period of two years, four student teams from different cohorts developed a note-taking app for four academic clients at the students’ own university. We investigated how projects involving internal clients can give students the benefits of engaging in real software development while also giving them experience of a student-staff collaboration that has its own benefits for students, academics, and the university more broadly. As the university involved is a Sino-Foreign university located in China, where most students are Chinese and most teaching staff are not, this ‘student as co-producer’ approach interacts with another feature of the project: cultural distance. Based on analysis of notes, reports, interviews, and focus groups, we recommend that students should be provided with communicative strategies for dealing with academics as clients; universities should develop policies on ownership of student-staff collaborations; and projects should include a formalised handover process. This article can serve as guidance for educators considering a ‘students as co-producers’ approach for software development projects.